Impaired skeletal muscle health in Parkinsonian syndromes: clinical implications, mechanisms and potential treatments - Kate T. Murphy; Gordon S. Lynch (Wiley, 2023)
Abstract There is increasing evidence that neurodegenerative disorders including the Parkinsonian syndromes are associated with impaired skeletal muscle health, manifesting as wasting and weakness. Many of the movement problems, lack of muscle strength and reduction in quality of life that are characteristic of these syndromes can be attributed to impairments in skeletal muscle health, but this concept has been grossly understudied and represents an important area of unmet clinical need. This review describes the changes in skeletal muscle health in idiopathic Parkinson's disease and in two atypical Parkinsonian syndromes, the most aggressive synucleinopathy multiple system atrophy, and the tauopathy progressive supranuclear palsy. The pathogenesis of the skeletal muscle changes is described, including the contribution of impairments to the central and peripheral nervous system and intrinsic alterations. Pharmacological interventions targeting the underlying molecular mechanisms with therapeutic potential to improve skeletal muscle health in affected patients are also discussed. Although little is known about the mechanisms underlying these conditions, current evidence implicates multiple pathways and processes, highlighting the likely need for combination therapies to protect muscle health and emphasizing the merit of personalized interventions for patients with different physical capacities at different stages of their disease. As muscle fatigue is often experienced by patients prior to diagnosis, the identification and measurement of this symptom and related biomarkers to identify early signs of disease require careful interrogation, especially for multiple system atrophy and progressive supranuclear palsy where diagnosis is often made several years after onset of symptoms and only confirmed post‐mortem. We propose a multidisciplinary approach for early diagnosis and implementation of personalized interventions to preserve muscle health and improve quality of life for patients with typical and atypical Parkinsonian syndromes.